Solving the problems of the adaptation system of Russian organizations based on foreign experience ("Journal "U". Economy. Management. Finance.", 2022)
Based on the material of modern texts of articles devoted to the foreign experience of personnel adaptation, the analysis of personnel adaptation systems was carried out on the example of companies in the USA, France and Japan. The paper analyzes various problems of personnel adaptation in Russian companies and ways to solve them. The purpose of the study was to answer the question: is it possible to solve problems with personnel adaptation in Russian organizations based on foreign experience.
Keywords: adaptation; personnel adaptation system; foreign experience; personnel